EMPOWERING APPROACHES BY CHINESE PARENTS OF SPECIAL NEED CHILDREN - Kyii, Wong (PEOPLE: International Journal of Social Sciences, 2017)
There is a large variation in the experience of caring for special need children. The objective of this study was to identify the empowering approaches of Chinese parents related to their care-giving experience.17 Chinese parents from 16 families whose children are attending a private school and a learning centre were interviewed in this study. A semi-structured face-to-face interview was used and responses were coded using grounded theory to identify themes of empowering approaches. Being cognitively and psycho-emotionally grounded enables Chinese parents to make sound decisions. The overwhelming needs related to caring for their special need child impel them to remain pragmatic when making appraisals. Their concern about the future of their child urges them to adopt a proactive approach. Interventional services aimed at helping Chinese parents to care for their special need child should include initiatives of empowering them to adopt positive approaches. Future research should look into the effectiveness of these approaches when adopted by novice parents.